2021
DOI: 10.1186/s12880-021-00547-x
|View full text |Cite
|
Sign up to set email alerts
|

A PET imaging study of the brain changes of glucose metabolism in patients with temporal lobe epilepsy and depressive disorder

Abstract: Background This study aims to compare the difference of the brain changes of glucose metabolism between temporal lobe epilepsy patients (TLE) with major depressive disorder and temporal TLE without major depressive disorder. Methods A total of 24 TLE patients, who met the inclusion criteria of our hospital, were enrolled in this study. They were divided into a TLE with depression group (n = 11) and a TLE without depression group (n = 13), according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, this is the first study investigating the metabolic correlates of TTH using [ 18 F]FDG PET within a cohort of BC patients. While it can be speculated that hypometabolism in the right insular areas may represent an [ 18 F]FDG PET trademark of TTH, other possible pre-existing or concomitant conditions, including BC itself, should be considered [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. In the first sense, in our sample of BC patients, TTH subjects were more affected by headache days and exhibited PET activity similar to that observed in MiG patients with a higher headache burden.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study investigating the metabolic correlates of TTH using [ 18 F]FDG PET within a cohort of BC patients. While it can be speculated that hypometabolism in the right insular areas may represent an [ 18 F]FDG PET trademark of TTH, other possible pre-existing or concomitant conditions, including BC itself, should be considered [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. In the first sense, in our sample of BC patients, TTH subjects were more affected by headache days and exhibited PET activity similar to that observed in MiG patients with a higher headache burden.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that the FC of the right dorsal putamen seed and the bilateral posterior central gyrus was lower in TLE patients than in controls which suggested that these patients may have an impaired putamenposterior central gyrus connection. rs-fMRI studies have shown that patients with TLE exhibit a reduced spontaneous activity in the posterior central gyrus [31] alongside hypometabolism [32] , and reduced blood perfusion [33] . Moreover, studies have proposed that abnormal activity of the posterior central gyrus may affect the sensory processing of the sensorimotor network, leading to sensory disturbances in patients with TLE [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that local glucose metabolism increases in the left dorsal prefrontal cortex and anterior cingulate cortex were observed by 18F-PET/CT in patients with refractory depression after treatment, which is highly correlated with the improvement of depression ( 15 ). In the past, abnormal glucose metabolism in the brain of patients with various malignant tumors has been detected by 18F-PET/CT ( 16 , 17 ), which suggests that there may be tumor-related depression. PET/CT is commonly used in tumor diagnosis, and tumor patients are often accompanied by emotional abnormalities.…”
Section: Introductionmentioning
confidence: 99%